Нові сполуки Sr₂LnB^IIISnO₇ (B^III — Sc, In) з двошаровою перовськітоподібною структурою - Тітов, Ю.О.; Білявина, Н.М.; Марків, В.Я.; Слободяник, М.С.; Полубінський, В.В. (Доповіді НАН України, 2015)
Визначенi границi областей iз шаруватою перовськiтоподiбною структурою (ШПС)
в рядах сполук типу Sr₂LnB^IIISnO₇ (B^III — Sc, In). Твердофазним синтезом iз еквiмолярних сумiшей Sr₃Sn₂O₇ + SrLn₂Sc₂O₇ i Sr₂SnO₄ + LnInO₃ синтезованi новi скандатостанати Sr₂LnScSnO₇ (Ln — La, Pr), iндатостанати Sr₂LaInSnO₇ (Ln — La, Pr) та
методом Рiтвельда визначена їх кристалiчна ШПС. Встановлена належнiсть ШПС
Sr₂LaScSnO₇ до структурного типу SrLn₂Sc₂O₇ (пр. гр. Fmmm), а ШПС Sr₂PrScSnO₇ i Sr₂LnInSnO₇ до структурного типу BaLa₂In₂O₇ (пр. гр. P4₂/mnm). Проаналiзованi особливостi будови ШПС синтезованих Sr₂LnB^IIISnO₇ (B^III — Sc, In). Определены границы областей со слоистой перовскитоподобной структурой (СПС) в рядах соединений типа Sr₂LnB^IIISnO₇ (B^III — Sc, In). Твердофазным синтезом из эквимолярных смесей Sr₃Sn₂O₇ + SrLn₂Sc₂O₇ и Sr₂SnO₄ + LnInO₃ синтезированы новые скандатостаннаты Sr₂LaInSnO₇ (Ln — La, Pr), индатостаннаты Sr₂LaInSnO₇ (Ln — La, Pr)
и методом Ритвельда определена их кристаллическая СПС. Установлена принадлежность
СПС Sr₂LaScSnO₇ к структурному типу SrLn₂Sc₂O₇ (пр. гр. Fmmm), а СПС Sr₂PrScSnO₇
и Sr₂LnInSnO₇ к структурному типу BaLa₂In₂O₇ (пр. гр. P4₂/mnm). Проанализированы
особенности строения СПС синтезированных Sr₂LnB^IIISnO₇ (B^III — Sc, In). The boundaries of regions with layered perovskite-like structure (LPS) in the rows of compounds
Sr₂LnB^IIISnO₇-type (B^III — Sc, In) are determined. The new scandatostannates Sr₂LnScSnO₇
(Ln La, Pr) and indatostannates Sr₂LaInSnO₇ (Ln — La, Pr) have been synthesized by the
solid-phase sintering from equimolar mixtures Sr₃Sn₂O₇SrLn₂Sc₂O₇ and Sr₂SnO₄ + LnInO₃, and
their crystal LPSs are determined by the Rietveld method. It is found that the LPS of Sr₂LaScSnO₇
belongs to the SrLn₂Sc₂O₇-type structure (sp. gr. Fmmm), and the LPSs of Sr₂PrScSnO₇ and
Sr₂LnInSnO₇ belong to the BaLa₂In₂O₇-type structure (sp. gr. P4₂/mnm). The peculiarities of
LPSs of Sr₂LnB^IIISnO₇ (B^III — Sc, In) are analyzed.